2015
DOI: 10.1002/ana.24429
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenetic study implicates SLC9a9 in multiple sclerosis disease activity

Abstract: This study identifies and validates the role of rs9828519, an intronic variant in SLC9A9, in IFNβ-treated subjects, demonstrating a successful pharmacogenetic screen in MS. Functional characterization suggests that SLC9A9, an Na(+) -H(+) exchanger found in endosomes, appears to influence the differentiation of T cells to a proinflammatory fate and may have a broader role in MS disease activity, outside of IFNβ treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…[29][30][31] For example, one study reported the discovery and validation of an intronic variant in SLC9A9 gene as a predictor of response to treatment (P <5 × 10 −8 ). 32 Currently, in the absence of strongly predictive prospective markers, treatment monitoring plays a major role. In fact, unquestionably, the currently best developed example of personalised medicine in MS is for safety monitoring of natalizumab treatment.…”
Section: Personalised Medicine For Multiple Sclerosis: Is It Needed?mentioning
confidence: 99%
“…[29][30][31] For example, one study reported the discovery and validation of an intronic variant in SLC9A9 gene as a predictor of response to treatment (P <5 × 10 −8 ). 32 Currently, in the absence of strongly predictive prospective markers, treatment monitoring plays a major role. In fact, unquestionably, the currently best developed example of personalised medicine in MS is for safety monitoring of natalizumab treatment.…”
Section: Personalised Medicine For Multiple Sclerosis: Is It Needed?mentioning
confidence: 99%
“…At present, it is not well known which pathways are activated during relapses and which ones are critical for defining a more active disease activity [5]. Previous gene expression studies have identified several genes such as GPR3, NFKB, SOCS3, STAT3, STAT1, CX3CR1, IDO, SLC9A9, HO-1 among others, associated with a more active disease [6][7][8][9][10][11][12][13][14][15][16]. However, at present none of such genes have been validated as a known biomarker of disease activity in MS and also, the pathways driving a more active disease are not well known [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Now, a new study by Federica Esposito and colleagues presents evidence that patient responses to IFN-β can be genetically determined. 3 Several previous studies have investigated whether single nucleotide polymorphisms (SNPs)-common genetic variants scattered throughout the genome-are associated with the response to IFN-β treatment in patients with MS. 4 Although many studies have reported associations between SNPs and treatment response, none of these associations have been confirmed in independent studies. Indeed, in two previous genome-wide association studies (GWAS) of the response to IFN-β treatment, there was essentially no overlap in the identified SNPs.…”
mentioning
confidence: 99%
“…3 The authors first conducted a GWAS in 146 Italian patients with MS. During 2 years of treatment with IFN-β, patients were classified as responders, partial responders or nonresponders according to clinical and MRI data. The analysis showed that the SNP rs9828519 was associated with an increased risk of nonresponsiveness to IFN-β treatment, with the number of nonresponders directly corresponding to the number of G alleles.…”
mentioning
confidence: 99%
See 1 more Smart Citation